Novel application of a Z-scheme photocatalyst of Ag3PO4@g-C3N4 for photocatalytic fuel cells. (15th January 2020) - Yu, Hongbin; Xue, Yanan; Lu, Ying; Wang, Xinhong; Zhu, Suiyi; Qin, Weichao; Huo, Mingxin
Abstract: A composite of Ag3 PO4 @g-C3 N4 with the Z-scheme structure was synthesized, and used as the photoanode in a photocatalytic fuel cell (PFC). With the help of the Z-scheme design, both the degradation of tetracycline and the output of maximum power density ( P max ) were greatly enhanced in this PFC system. The degradation rate of tetracycline in the Ag3 PO4 @g-C3 N4 PFC was 2.53 times and 3.65 times that in the PFC systems with the Ag3 PO4 photoanode and the g-C3 N4 photoanode, respectively. The P max of the Ag3 PO4 @g-C3 N4 PFC was 6.06 μW cm −2, which was 1.46 times and 90.4 times that of the Ag3 PO4 PFC (4.16 μW cm −2 ) and the g-C3 N4 PFC (0.067 μW cm −2 ), respectively. The possible mechanism was proposed. The Z-scheme photoanode could not only contribute to the separation of photogenerated carriers to achieve a high photocatalytic activity, but also reserve a good redox capacity. Additionally, aeration played an important role on the PFC performance. It was demonstrated that N2 purging facilitated the electricity generation, while O2 purging promoted the pollutant degradation. Graphical abstract: Image 1 Highlights: Novel application of Z-scheme photocatalysts for photocatalytic fuel cells (Z-PFC). Greatly enhanced P max and TC degradation were simultaneously realized in the Z-PFC. N2 purging facilitates electricity generation. O2 purging promotes pollutant degradation.